Crowd‐sourced and incentive-driven UAV system to assist with network slices - Benhamza, Boutheina; Benchettouh, Douaa Nour Elhouda; Bouzid, Tarek (Laghouat : Université Amar Telidji - Département d'informatique, 2025)
This thesis presents a study aimed at improving the performance of wireless networks using unmanned aerial vehicles UAVs within a 5G network environment. It focuses on the concept of network slicing which allows part of the network infrastructure to be used to serve the needs of different services . The thesis also aims to resolve issues that UAVs might face during operation such as low battery, band congestion or sudden unavailability by integrating backup UAVs into the system. A proposed model was designed based on an advanced system that ensures service continuity and achieves the maximum level of user satisfaction through algorithms that select the most appropriate backup UAV based on conditions such as battery capacity and the type of services provided, while ensuring reasonable pricing for users. The study includes a system model using the UML activity diagrams and the implementation of the proposed algorithms by MATLAB to demonstrate the effectiveness of the proposed solutions compared to the previous system. The results showed that the system improved much better in the percentage of connected users and their non abandoned, especially in emergency situations or when the number of users increases suddenly. Finally, this thesis contributes scientifically to the field of integrating UAVs with 5G networks and represents a step for developing flexible and highly efficient communications systems that serve future requirements in multiple fields.